Public policies for rural education: Pronera, Procampo and Pronacampo - Santos, Ramofly Bicalho dos; Silva, Marizete Andrade da (Revista Eletrônica de Educação, 2016)
The central objective of this article is to present reflections about three specific public policies regarding Education in rural areas in Brazil: the National Education Program in Agrarian Reform Areas (Pronera), integrated into the Ministry of Agrarian Development; the Higher Education Support Program for a Graduation Course in Rural Education (Procampo) and the National Program of Rural Education (Pronacampo), all linked to the Ministry of Education. Arising from the mobilization of social movements and organizations, these policies show that the struggle for agrarian reform transcends the struggle for land, since it includes the occupation of many other spaces. Within this work, we carried out a simple approach of the context that resulted in the Rural Education, indicating the main aspects of the studied programs. We developed a bibliographical and documentary research, using among the sources of research, legislation, regulations and decrees, as well as some references recently produced in the field of education in Brazil. We conclude that the collective production of knowledge in association with students, educators, communities and social movements of struggle for land, can dialogue with stories, memories, identities, desires, values and recognition, strengthening the debate on rural education in its close relationship with the social movements, rural schools and public universities. We realized that this articulation is one of the main challenges to be faced by the Movement on rural education and in the results consolidation of Pronera, Procampo and Pronacampo. Keywords: Rural Education. Pronera. Procampo. Pronacampo.